Innovative Equitable Profit-Sharing Schemes for Optimizing Cattle Farming Income: An Integrative Approach Based on Islamic Law - Pertiwi, Ana; Sunarti, Zeni; Haeran; Musthofa , M. Arif; Kartika Devi, Erwina (CV. Civiliza Publishing, 2025)
This study explores the effective implementation of the profit-sharing mechanism based on the mudharabah contract in cattle farming enterprises in Parit Culum II Village, Indonesia, aiming to overcome capital constraints and enhance farmers’ income. Employing a qualitative descriptive approach, the research combines empirical and normative juridical methods, utilizing field observations, interviews, and document analysis. The findings reveal that the mudharabah model fosters a synergistic partnership between capital providers (shahibul maal) and farmers (mudharib), where profits are shared proportionally and financial risks borne mainly by capital owners, unless managerial negligence occurs. Notably, the study uncovers an innovative profit-sharing scheme involving both monetary returns and proportional division of livestock offspring, promoting sustainable biological asset management. This application extends fiqh muamalah into the agribusiness sector, emphasizing justice (‘adl), trustworthiness (amanah), and maqashid al-shari’ah principles to establish transparent and equitable partnerships. The research highlights the importance of enhanced monitoring, communication, and Shariah-based managerial training to optimize partnership sustainability. This model offers practical insights for advancing inclusive and sustainable Shariah-compliant economic development in rural agrarian communities